Research of trends in the cryptocurrency market as a basis for ensuring financial stability and development of retail companies - Sosnov, Ihor; Zastola, Yevhen; Chernov, Oleksandr (Center for Tech and Media Research, 2025)
Financial stability largely determines the possibility of successful and continuous business development. The key factor is proper financial support. In particular, for retail companies, such support allows maintaining an acceptable level of product range to meet the demand and needs of potential buyers. To solve the problem of financial support, one of the sources of raising funds is the stock market. This market allows using various tools to achieve the set goals. One of these tools is cryptocurrency, which allows both attracting the necessary resources and hedging possible risks. Based on this, the work examines the main trends of individual segments of the cryptocurrency market. At the same time, an analysis of the relationship between individual segments of the cryptocurrency market and the dynamics of shares of individual retail companies is carried out. For these purposes, the wavelet coherence methodology is considered. The results of the work are presented in the form of various graphs and diagrams, which allows you to understand the course of the study, assess its reliability.
Keywords: development; research; trends; cryptocurrency; funding; sustainability; trading; benchmarking